‘Sri lankan english’, ‘speak english our way’ and ‘the other’ - Ibrahim, R. (University of Jaffna, 2012)
The variety of English spoken in Sri Lanka is defined as ‘Sri Lankan English’ by scholars who have attributed this variety with distinguished features that are both linguistic and ideological. There is also a consensus in these ‘academic’ and ‘non academic’ circles that the English language is a symbol of power and hegemony in the Sri Lankan society. Accordingly, the programme that was launched in 2009 called ‘Speak English Our Way’ was meant to dethrone the dominant position of English and replace it with a more ‘native’ variety. Yet, in the definition of Sri Lankan and its nativization process, there is an absence in the representation of the ‘other’ or the marginalized groups. It is because the Sri Lankan variety of English or Sri Lankan English has been defined as Standard Sri Lankan English or the normative variety which represents the class affinities of the urban English speaking elite. Also, this variety is marked by the heavy influence of Sinhala and not Tamil. Thus, this variety is both ethno-centric and class biased. Also, when it is used in prescriptive forms like in the case of language learning, it clearly favours the dominant ideology, suppressing the voice of ‘the other’.